Page 1

Applied Mathematics and Sciences: An International Journal (MathSJ ), Vol. 3, No. 1, March 2016

A STUDY ON L-FUZZY NORMAL SUB l -GROUP 1 1

K.Sunderrajan, 2A.Senthilkumar and 3R.Muthuraj

SRMV College of Arts and Science, Coimbatore-641020, Tamilnadu, India. 2 SNS College of Technology , Coimbatore-641035 , Tamilnadu, India. 3 H.H.The Rajah’s College,Pudukkottai-Tamilnadu, India

ABSTRACT This paper contains some definitions and results of characteristics.

L-fuzzy normal sub l -group and its generalized

KEYWORDS Fuzzy set, L -fuzzy set, L-fuzzy sub

l --group, L-fuzzy normal sub l -group .

AMS Subject Classification (2000): 06D72, 06F15, 08A72.

1.INTRODUCTION L. A. Zadeh[11] introduced the notion of fuzzy subset of a set S as a function from X into I = [0, 1]. Rosenfeld[2] applied this concept in group theory and semi group theory, and developed the theory of fuzzy subgroups and fuzzy subsemigroupoids respectively J.A.Goguen [6] replaced the valuations set [0, 1],by means of a complete lattice in an attempt to make a generalized study of fuzzy set theory by studying L-fuzzy sets.. In fact it seems in order to obtain a complete analogy of crisp mathematics in terms of fuzzy mathematics, it is necessary to replace the valuation set by a system having more rich algebraic structure. These concepts l -groups play a major role in mathematics and fuzzy mathematics. G.S.V Satya Saibaba [9] introduced the concept of L- fuzzy sub l -group and L-fuzzy l -ideal of l group. In this paper, we initiate the study of L-fuzzy normal sub l -groups .

2.PRELIMINARIES This section contains some definitions and results to be used in the sequel.

2.1. Definition [5,6,7] A lattice ordered group ( l -group) is a system G= (G, *, ≤ ) where i (G, *) is a group ii (G , ≤ ) is a lattice iii the inclusion is invariant under all translations x→ a + x+ b i.e. x≤ y ⇒ a+ x+ b ≤ a + y + b, for all

DOI : 10.5121/mathsj.2016.3101

a, b∈G.

1


Applied Mathematics and Sciences: An International Journal (MathSJ ), Vol. 3, No. 1, March 2016

2.2 .Definition [11] Let X be a non-empty set. A fuzzy subset A of X is a function A : X → [ 0, 1 ].

2.3. Definition [1,2] An L-fuzzy subset A of G is called an L-fuzzy subgroup (ALFS) of G if for every x,y ∈ G, i ii

A(xy ) ≥ A(x) ˅ A(y) A(x-1) = A (x).

2.4. Definition [9,10] An L-fuzzy subset A of G is said to be an L-fuzzy sub l - group(LFS l ) of G if for any x , y ∈ G

i. ii. iii. iv.

A(xy) ≥ A(x) ˅ A(y) A(x -1) = A(x) A(x∨y) ≥ A(x) ˅ A(y) A(x∧y) ≥ A(x) ˅ A(y).

2.5. Definition [4] Let G and G′ be any two groups. Then the function f: G → G′ is said to be a homomorphism if f (xy) = f (x) f (y) for all x, y in G.

2.6.Definition[3] Let G and G′ be any two groups (not necessarily commutative). Then the function f: G → G′ is said to be an anti-homomorphism if f (xy) = f (y) f (x) for all x, y in G. Remark: A homomorphism may or may not be an anti-homomorphism

2.7 .Definition [8,10] A sub l -group H of an l - group G is called a normal sub l -group of G if for all x in G and h in H we have xhx-1 ∈ H .

2.8.Definition[8,10 ] An L-fuzzy sub l -group A of G is called an L-fuzzy normal sub l -group (LFNS l G) of G if for every x, y∈G, A(xyx-1) ≥ A(y). 2


Applied Mathematics and Sciences: An International Journal (MathSJ ), Vol. 3, No. 1, March 2016

3. PROPERTIES OF AN L-FUZZY NORMAL SUB l -GROUP In this section, we discuss properties of an L-fuzzy normal sub l -group

3.1.Theorem Let G be an l -group and A be an L-fuzzy sub l -group of G, then the following conditions are equivalent. i. A is an L-fuzzy normal sub l -group of G. ii. A(xyx-1) = A(y), for all x, y ∈G. iii. A(xy) = A(yx), for all x, y ∈G. iv. Proof: i ⇒ ii. Let A is an L-fuzzy normal sub l -group of G. Then A(xyx-1) ≥ A(y) for all x, y∈G. By taking advantage of the arbitrary property of x, we have, A(x-1y(x-1)-1)

≥ A(y).

Now, A(y) = A(x-1 (xyx-1)(x-1)-1) = A(xyx-1) ≥ A(y). Hence, A(xyx-1)

= A(y) for all x, y ∈G. ii ⇒ iii.

Let A(xyx-1) = A(y), for all x, y ∈G. Taking yx instead of y, we get, A(xy )

Let

= A(yx), for all x, y ∈G. iii ⇒ i.

A(xy) = A(yx), for all x, y ∈G. A(xyx-1) = A(yxx-1) = A(y) ≥ A(y).

Hence, A is an L-fuzzy normal sub l -group of G.

3


Applied Mathematics and Sciences: An International Journal (MathSJ ), Vol. 3, No. 1, March 2016

3.2 .Theorem Let A be an L-fuzzy subset of an l -group G. If A(e) = 1 and A(xy-1) ≥ A(x) ∧ A(y) , A(x ∨ y) ≥ A(x) ∧ A(y), A(x ∧ y) ≥ A(x) ∧ A(y) and A(xy) = A(yx), for all x and y in G, then A is an Lfuzzy normal sub l -group of a group G, where e is the identity element of G. Proof: Let e be identity element of G and x and y in G. Let A(e) = 1 and A(xy-1) Now,

A(x-1)

Therefore, A(x-1)

≥ A(x) ∧ A(y), for all x and y in G.

= A (ex-1) ≥ A (e) ∧ A (x) ≥ 1 ∧ A(x) = A(x) ≥ A(x), for all x in G.

Hence, A((x-1)-1) ≥ A(x-1) and A(x) ≥ A(x-1). Therefore, A(x-1) = A(x), for all x in G. Now, replace y by y-1, then A(xy) = A( x(y-1) -1) ≥ A(x) ∧ A(y-1) = A(x) ∧ A(y), for all x and y in G. A(xy) ≥ A(x) ∧ A(y), for all x and y in G. Also, we have, A(x ∨ y) ≥ A(x) ∧ A(y), A(x ∧ y) ≥ A(x) ∧ A(y). Hence, A is an L-fuzzy sub l -group of an l -group G. Since, A(xy) = A(yx) for all x and y in G, A is an L-fuzzy normal sub l -group of an l -group G.

3.3 .Theorem If A is an L-fuzzy normal sub l -group of an l -group G, then empty or a normal sub l -group of G.

H = {x / x∈G: A(x) = 1} is either

Proof It is clear from theorem 3.2

4


Applied Mathematics and Sciences: An International Journal (MathSJ ), Vol. 3, No. 1, March 2016

3.4 .Theorem If A is an L-fuzzy normal sub l -group of an l -group G, then H = {x∈G : A(x) = A(e)} is either empty or a normal sub l -group of G, where e is the identity element of G. Proof Since , H is a sub l -group of G. Now, let for any x in G and y in H, A(xyx-1) = A(y) = A(e). Since A is an LFNS l G of an l -group G and y∈H. Hence, xyx-1∈G and H is a normal sub l -group of G. Hence, H is either empty or a normal sub l -group of an l -group G.

3.5 .Theorem If A and B are two L-fuzzy normal sub l -groups of an l -group G, then their intersection A ∩ B is an L-fuzzy normal sub l -group of G. Proof Let x and y belong to G. i.

(A ∩ B) (xy) = A(xy) ∧ B(xy) ≥ { A(x) ∧ A(y) } ∧ { B(x) ∧ B(y) } ≥ { A(x) ∧ B(x) } ∧ { A(y) ∧ B(y) } = (A ∩ B) (x) ∧ (A ∩ B) (y).

Therefore, (A ∩ B) (xy) ≥ (A ∩ B)(x) ∧ (A ∩ B) (y), for all x and y in G. ii.

Therefore, iii.

Therefore, iv.

(A ∩ B)(x-1) = A(x-1) ∧ B(x-1) = A(x) ∧ B(x) = (A ∩ B)(x). (A ∩ B) (x-1)

= (A ∩ B)(x), for all x in G.

(A ∩ B) (x ∨ y) = A(x ∨ y) ∧ B(x ∨ y) ≥ { A(x) ∧ A(y) } ∧ { B(x) ∧ B(y) } ≥ { A(x) ∧ B(x) } ∧ { A(y) ∧ B(y) } = (A ∩ B) (x) ∧ (A ∩ B) (y). (A ∩ B) (x ∨ y) ≥ (A ∩ B)(x)∧(A ∩ B)(y), for all x and y in G. (A ∩ B) (x ∨ y) = A(x ∨ y) ∧ B(x ∨ y) 5


Applied Mathematics and Sciences: An International Journal (MathSJ ), Vol. 3, No. 1, March 2016

≥ { A(x) ∧ A(y) } ∧ { B(x) ∧ B(y) } ≥ { A(x) ∧ B(x) } ∧ { A(y) ∧ B(y) } = (A ∩ B) (x) ∧ (A ∩ B) (y). (A ∩ B) (x ∨ y) ≥ (A ∩ B)(x)∧(A ∩ B)(y), for all x and y in G.

Therefore,

Hence, A ∩ B is an L-fuzzy sub l -group of an l -group G. Now,

(A ∩ B) (xy) = A(xy) ∧ B(xy) = A(yx) ∧ B(yx), since A and B are LFNS l G of G. = (A ∩ B) (yx). (A ∩ B) (xy) = (A ∩ B) (yx).

Hence, A ∩ B is an L-fuzzy normal sub l -group of an l -group G. Remark The intersection of a family of L-fuzzy normal sub l -groups of an l -group G is an L-fuzzy normal sub l -group of an l -group G.

3.6 .Theorem If A is an L-fuzzy normal sub l -group of an l -group G if and only if A(x) = A(y-1xy), for all x , y ∈ G. Proof Let x and y be in G. Let A be an L-fuzzy normal sub l -group of an l -group G. Now,

A(y-1xy)

= A(y-1yx) = A(ex) = A(x).

Therefore,

A(x)

= A(y-1xy), for all x and y in G.

Conversely, assume that

A(x)

= A(y-1xy).

Now,

A(xy) = A(xyxx-1) = A(yx)

Therefore, A(xy) = A(yx), for all x and y in G. Hence, A is an L-fuzzy normal sub l -group of an l -group G.

6


Applied Mathematics and Sciences: An International Journal (MathSJ ), Vol. 3, No. 1, March 2016

3.7 .Theorem Let A be an L-fuzzy sub l -group of an l -group G with A(y) < A(x), for some x and y in G, then A is an L-fuzzy normal sub l -group of an l -group G. Proof Let A be an L-fuzzy sub l -group of an l -group G. Given A(y) < A(x), for some x and y in G, A(xy) ≥ A(x) ∧ A(y), as A is an LFS l G of G = A(y); and A(y) = A(x-1xy) ≥ A(x-1) ∧ A(xy) ≥ A(x) ∧ A(xy), as A is an LFS l G of G = A(xy). A(y) ≥ A(xy) ≥ A(y). Therefore, A(xy) = A(y), for all x and y in G. and,

A(yx) ≥ A(y) ∧ A(x), as A is an LFS l G of G = A(y); and A(y)

A(y)

= A(yxx-1) ≥ A(yx) ∧ A(x-1) ≥ A(yx) ∧ A(x), as A is an LFS l G of G = A(yx). ≥ A(yx) ≥ A(y).

Therefore, A(yx) = A(y), for all x and y in G. Hence, A(xy) = A(y) = A(yx), for all x and y in G. Hence, A(xy) = A(yx), for all x and y in G. Hence, A is an L-fuzzy normal sub l -group of an l -group of G.

3.8 .Theorem Let A be an L-fuzzy sub l -group of an l -group G with A(y) > A(x) for some x and y in G, then A is an L-fuzzy normal sub l -group of an l -group G. Proof It is clear from theorem 3.7

7


Applied Mathematics and Sciences: An International Journal (MathSJ ), Vol. 3, No. 1, March 2016

REFERENCES [1]

Anthony.J.M, Sherwood.H, A characterization of fuzzy subgroups, Fuzzy sets and systems, 7 (1982), 297-305. [2] Azriel Rosenfeld, Fuzzy Groups, Journal of mathematical analysis and applications, 35, 512-517 (1971). [3] Biswas.R, Fuzzy subgroups and anti fuzzy subgroups, Fuzzy Sets and Systems 35 (1990) 121 â&#x20AC;&#x201C; 124. [4] Choudhury.F.P, Chakraborty.A.B and Khare.S.S, A note on fuzzy subgroups and fuzzy homomorphism, Journal of mathematical analysis and applications, 131, 537-553 (1988). [5] Garrett Birkhof : Lattice Theory, American Mathematical Society colloquium publications, Volume XXV. [6] J.A. Goguen : L-fuzzy sets, J.Math.Anal.Appl. 18, 145-174 (1967). [7] V. Murali : Lattice of fuzzy algebras and closure systems in I X, Fuzzy sets and systems 41, 101-111 (1991). [8] Mukherjee.N.P and Bhattacharya.P : Fuzzy normal subgroups and fuzzy cosets, inform.Sci 34 (1984), 225-239. [9] Satya Saibaba.G.S.V, Fuzzy Lattice Ordered Groups, Southeast Asian Bulletin of Mathematics , 32, 749-766 (2008). [10] K.Sunderrajan, A.Senthilkumar, Properties of L-fuzzy normal sub -groups, General Mathematical Notes , Vol. 22, No. 1, May 2014, pp. 93-99. [11]L.A. Zadeh : Fuzzy sets, Inform and control, 8, 338-353 (1965).

8

A STUDY ON L-FUZZY NORMAL SUBl -GROUP  

This paper contains some definitions and results of L-fuzzy normal sub l -group and its generalized characteristics.

A STUDY ON L-FUZZY NORMAL SUBl -GROUP  

This paper contains some definitions and results of L-fuzzy normal sub l -group and its generalized characteristics.

Advertisement